MO550INDOXYL SULFATE AFFECTS ERYTHROPOIESIS DURING THE COURSE OF CHRONIC KIDNEY DISEASE: A MOLECULAR STUDY. (29th May 2021) - Hamza, Eya; Ouled-Haddou, Hakim; Jankovsky, Nicolas; Demont, Yohann; Brigant, Benjamin; Massy, Ziad; Burtey, Stéphane; Choukroun, Gabriel; Garçon, Loïc; Metzinger, Laurent; Metzinger-le Meuth, Valérie
Abstract: Background and Aims: Chronic kidney disease (CKD) is a global health condition characterized by a progressive deterioration of renal function due to high serum levels of uremic toxins. Anemia is a major trouble in CKD patients that contributes to a faster deterioration of renal failure, leading to cardiovascular disease and increasing morbimortality. Erythropoietin (EPO) is known to contribute to CKD-associated anemia. Thus, accumulation of uremic toxins in blood impairs EPO synthesis, leading to a subsequent impairment of erythropoiesis in the bone marrow. Very few molecular clues explain why erythropoiesis is affected in CKD or explain why erythropoiesis-stimulating agents (ESA) are not efficient in some patients with CKD. The current study aims to characterize the impact of one of the most representative uremic toxins, Indoxyl Sulfate (IS), in CKD-related anemia. IS is a protein-bound uremic toxin derived from the tryptophan dietary metabolism which is difficult to remove by dialysis. Our study demonstrates the molecular effects of IS on the growth and the differentiation of red blood cells in an erythroid cell line and in primary cell cultures CD34+. Method: Firstly, we examined in vitro the time-courses of IS under clinically relevant concentrations of IS (250 µM -1 mM) in a human leukemic cell line in which proliferation is induced by EPO, the UT7/EPO cell line. Cell apoptosis, proliferation, differentiation and cell cycle analysis were assessed by the MACSQuant flow cytometry. Erythroid gene expression analysis was assessed by RT-qPCR (Quantstudio 7 flex). The ratio A260/280 assessed the quality of nucleic acids. Western blotting experiments were performed to study protein expression. Human primary CD34+ cells were obtained from mobilized peripheral blood mononuclear cells (MNC) of healthy subjects and were isolated by magnetic microbeads separation on MACS columns. Results: IS at 250 µM and 1 mM increased apoptosis of UT7/EPO cell line at 48h compared to control condition. On the other hand, we found no significant effect of IS on the phenotype of UT7/EPO, when using CD235a (Glycophorin A), as a marker for the detection of the erythroid cell lineage. Ki67 cellular levels, a cell proliferation marker, was not altered between control and IS experiments. This indicated that IS did not affect proliferation in UT7/EPO. At 48h, at the clinically relevant concentration of IS (250 µM), we observed an increase of the cell phase cycle Sub-G1. The analysis of erythropoiesis related genes shows that HIF2α was deregulated with IS (250 µM). Finally, in the Epo-EpoR signalling pathway, we studied the activation of the Jak2/Stat5 proteins. Results in human primary CD34+ cells confirmed the apoptotic effect of IS observed in UT7/EPO. Conclusion: Our findings suggest that IS, a representative protein-bound uremic toxin, could affect cell viability, apoptosis and the cell cycle. This study suggests clues to develop new therapies for CKD-associated anemia.